Reflecting on an academic career: associations between past mentoring investments and career benefits. Issue 5 (20th October 2021) - Boeder, Jordan; Fruiht, Veronica; Erikson, Kevin; Hwang, Sarah; Blanco, Giovanna; Chan, Thomas
ABSTRACT: Receiving mentoring is associated with lasting career benefits ; however, less is known about long-term career gains for mentors. A national sample of retired academics were surveyed to examine associations between past mentoring behaviors and current evaluations of their careers. Participants ( N = 277) were on average 73.6 ( SD  = 6.2) years old with 34.9 ( SD  = 8.0) years of occupational tenure and 7.7 ( SD  = 5.8) years post-retirement. Structural equation modeling results demonstrated that having more protégés ( β  = .19, p = .024) and engaging in more mentoring behaviors ( β  = .18, p = .027) were associated with objective career achievements. However, mentoring behaviors, and not the number of protégés, were linked to subjective career achievements (β = .33, p < .001). While prior research demonstrates that mentors experience short-term benefits from mentoring, the present study's findings suggest that mentors may also experience long-term objective and subjective career benefits.